Respon Masyarakat Terhadap Pelayanan Kantor Urusan Agama Pada Masa Pandemi Covid-19 di Kota Medan - Prasetia, Adji; Hidayah, Erika Nurul; Hanan, Aulia Fahira; Pratama, Rudi; Firmansyah, Heri (Ikatan Dai Indonesia, 2023)
Under the Ministry of Religion's aegis, the Office of Religious Affairs (KUA) serves Muslims by registering marriages and providing other services. In order to satisfy the community, KUA must always provide the best service possible as a service center. They were required to implement health protocols and maintain physical contact with prospective brides who wanted to register their marriage with the KUA during the Covid 19 pandemic. As a result, the issue that will be discussed in this article is the response that the general public gave to KUA services in Medan City during the Covid-19 pandemic. observation, interviews, and documentation are all methods of data collection. During the Covid 19 Pandemic, the results indicated that the community's response to services at the Medan City KUA was effective and favorable.